Evaluasi Kebijakan Perwali No.22 Tahun 2020 Tentang Pelaksanaan Pembatasan Sosial Berskala Besar Di Kota Makassar - Andi Tenri Rezki Oji; Samsualam; Sitti Patimah (Journal of Muslim Community Health, 2021)
Background: The mortality rate for COVID-19 in Indonesia is 8.9%, this figure is the highest in Southeast Asia. The Makassar city government issued a policy on the implementation of large-scale social restrictions through Makassar Mayor Regulation number 22 of 2020 concerning the Implementation of Scaled Social Restrictions Big in Makassar City, South Sulawesi Province, this policy is an effort to respond to COVID 19 by the Makassar city-regional government. Method: This research method is qualitative. Data collection using observation and in-depth interviews (in-depth interviews) to evaluate Makassar Mayor Regulation number 22 of 2020 concerning the Implementation of Large-Scale Social Restrictions in Makassar City. Results: The results of this study explain the inputs, processes, and outputs of the Perwali Policy no.22 of 2020, which includes human resources determined by decree, creation of border posts, activity restrictions, policy funding from the APBD, policy implementation, policy effectiveness and efficiency, successful implementation. policies and reducing the number of Covid-19 cases. Conclusion: The existence of guardian policy no.22 of 2020 in the city of Makassar continues to reap the pros and cons of several circles, on the one hand, many people have expressed an attitude to encourage the implementation of PSBB where it can break the chain of transmission from Covid-19.